Stealth trading and volatility - Barclay, Michael J.; Warner, Jerold B. (Journal of Financial Economics, 1993)
We examine the proportion of a stock's cumulative price change that occurs in each trade-size category, using transactions data for a sample of NYSE firms. Although the majority of trades are small, most of the cumulative stock-price change is due to medium-size trades. This evidence is consistent with the hypothesis that informed trades are concentrated in the medium-size category, and that price movements are due mainly to informed traders' private information.